Synthesis and structural characterization of the vividly colored first row transition metal-containing oxyfluoride antiperovskites Sr3-xMnxMO4F and Sr3-xMnxMO4-αF1-δ (M = Al, Ga). (June 2018) - Quilty, Calvin D.; Avdeev, Maxim; Sullivan, Eirin
Graphical Abstract: Highlights: Substitution of Mn 2+ demonstrates Sr3- x Ax M O4 F can tolerate divalent first row transition metals. The colors of these materials vary from green to purple depending on anion stoichiometry. Intense colors are likely due to small amounts of Mn 3+ on the tetrahedral Al site. Structural data is consistent with preferential occupation of eight-coordinate Sr(2) site by Mn 2+ . Large off-center displacements are observed on the underbonded ten-coordinate Sr(1) site. Abstract: Incorporation of dopant amounts of the divalent transition metal cation Mn 2+ into the oxyfluoride material Sr3- x Mn x M O4 F ( M  = Al, Ga; 0 ≤  x  ≤ 0.1) yields green powders which vary in hue depending on the identity of M . Treatment of these phases with post-synthesis annealing under reducing conditions produces anion deficient phases according to Sr3- x Mn x M O4-α F1-δ displaying vivid purple coloration. Intense colors are likely due to small amounts of Mn 3+ on the tetrahedral M site. Full structural characterization based upon powder X-ray diffraction (PXRD), neutron powder diffraction (NPD), and thermogravimetric analysis (TGA) data are presented herein, demonstrating that the Sr3 -x Ax M O4 F ( A  = Ca, Sr, Ba; M  = Al, Ga) anti-perovskite structure can readily accommodate first row transition metals.